Cultura de segurança do paciente, estresse ocupacional e burnout em profissionais de unidades de perioperatório - Munhoz, Oclaris Lopes (2018)
Occupational stress and burnout syndrome are directly related to worker's illness, which can have consequences on the care provided and affect the safety culture of the patient. The object of this study is the association between occupational stress and burnout and its repercussions on the safety culture. From the research question: is there a relationship between occupational stress and burnout of health professionals about the perception of patient safety culture in perioperative units? -, this research aims to evaluate the relationship of occupational stress and burnout of health professionals with the safety culture in perioperative units. A cross-sectional study was carried out, with 146 health professionals working at the units: General Surgery Unit - Internment Service; Surgical ward; Anesthetic and Intermediate Recovery Room. To collect data, a tool was used to evaluate the biossocial characteristics, the work and health profile of the professionals studied, the Safety Attitude Questionnaire (SAQ) to evaluate the safety culture of the patient, the Job Stress Scale ( JSS) for occupational stress and the Maslach Burnout Inventory (IMB) for burnout syndrome. Data were collected from March to July 2018. Data analysis was performed using descriptive and inferential statistics, considering a significance level of 5% for all tests. Ethical precepts involving human research were followed. As results, there was a predominance of nursing technicians (50.7%), followed by nurses (20.5%) and physicians (14.4%), with a median age of 41.1 years. The majority of the professionals were female (n = 104, 71.2%), with companion (n = 112, 76.7%) and with children (n = 100, 68.5%). The highest prevalence was high school (n = 50, 34.2%). Regarding the safety culture, the health professionals of the perioperative units had a negative perception about the safety culture of the patient in these environments (mean = 63.8). Tracing the occupational stress scenario, the majority of participants had high psychological demands (n = 93, 63.7%) and low control over work (n = 83, 56.8%). There was a higher prevalence of health professionals in the high-demand quadrant (n = 59, 40.4%). Regarding burnout, 15 (10.3%) health professionals presented the syndrome. It was evidenced that health professionals who are in burnout have high psychological demands (p = 0.049). In summary, there was a low and negative correlation between depersonalization, psychological demand and perception of the patient's safety culture. That is, the better the result of one, the worse the other. Still, the professional achievement variable presented a low and positive correlation with the safety culture. That is, the greater the professional achievement, the greater the perception for positive culture. In addition, the data obtained revealed important circumstances of the occupational diseases to which the health professionals are exposed, which undermines the health of the worker and, consequently, weakens the care provided and compromises the safety culture of the patient.